2017
DOI: 10.14423/smj.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30-Day Mortality in Hospitalized Patients with Clostridium difficile Infection

Abstract: Advanced age, Charlson comorbidity index, intensive care unit status, and peptic ulcer disease are predictors of all-cause 30-day mortality in hospitalized patients with CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…We confirm that increasing age is an important risk factor for a fatal outcome of CDI, as described previously [ 20 , 21 ]. A systematic review which included 30 studies showed that increasing age is among the most reported risk factor for mortality in patients with CDI [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We confirm that increasing age is an important risk factor for a fatal outcome of CDI, as described previously [ 20 , 21 ]. A systematic review which included 30 studies showed that increasing age is among the most reported risk factor for mortality in patients with CDI [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the elderly are characterized by a greater number of chronic diseases, including those that contribute to a worse course of CDI, such as chronic kidney disease, diabetes, or malignancy [ 23 ]. Gender is not an important factor since the risk was similar for both males and females, as described in other studies [ 21 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The IDSA‐SHEA 7 and World Society of Emergency Surgery 37 reviewed their guidelines recently. The other guidelines are American College of Gastroenterology 2013, 38 European Society of Clinical Microbiology and Infectious Diseases 2014, 39 and Australasian Society of Infectious Diseases 2016 40 . The commonest severe CDI criteria in clinical guidelines were raised white blood cells, followed by low albumin and raised creatinine level.…”
Section: Resultsmentioning
confidence: 99%
“…However, when the authors differentiated studies according to methodology and quality of study, they identified age and the presence of comorbidities as the two most common severity predictors for CDI. CCI score was frequently used to assess comorbidity burden in several of the included studies [34][35][36][37][38]. Interestingly, even though the role of leukocytosis in severity classification is widely recognized, age and comorbidities (as depicted by validated scores such as the CCI score) are not included in any of the currently available international guidelines to define severe disease.…”
Section: Discussionmentioning
confidence: 99%